Boxing as type of martial art - Voronov N.A. (Interaktivnaâ Nauka, 2018)
origin of boxing and its formation from amateur boxing to professional is considered in article. As rules of conducting fight from Ancient Rome and as the boxing became the Olympic sport changed up to now is studied. The box demands from the fighter physical force and endurance, excellent reaction and coordination, the perfected equipment. Skills of the boxer are poured extremely effective in extreme situations when it is necessary to stand for itself, for the relatives, for justice.